COMPARATIVE ANALYSIS OF THE USAGE OF SIMILE IN ENGLISH AND UZBEK LANGUAGES (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article presents a comparative analysis of the usage of simile in English and Uzbek languages, exploring the similarities and differences in their structures, functions, and cultural implications. Simile, as a figure of speech that directly compares two different things, plays a vital role in enriching language and enhancing the expressive quality of both English and Uzbek. Through a systematic examination of literary texts, idiomatic expressions, and everyday language, this study aims to highlight how similes reflect cultural values, emotions, and social norms in both languages. By analyzing specific examples and drawing on linguistic theories, the article seeks to contribute to the understanding of cross-cultural communication and the dynamics of language use.